PENDIDIKAN KARAKTER BERBASIS INOVASI PADA SAAT BELAJAR DARING DI SDIT BANDAR LAMPUNG SELAMA MASA PANDEMI COVID-19 - Ruswanto; Kalsum , Umi; Sunarto (Research Institute and Community Engagement of UIN MADURA, 2024)
Thei Covid-19 paindeimic hais haid ai significaint impaict on vairious aispeicts of lifei, including thei eiducaition seictor. Thei closurei of schools aind thei shift to distaincei leiairning preiseinteid maijor chailleingeis in deiveiloping chairaicteir eiducaition ait Inteigraiteid Islaimic Eileimeintairy Schools (SDIT). This study aiims to eixplorei thei chailleingeis aind innovaitions impleimeinteid in chairaicteir eiducaition ait Inteigraiteid Islaimic Eileimeintairy Schools (SDIT) Peirmaitai Bundai aind Inteigraiteid Islaimic Eileimeintairy Schools (SDIT) Peilitai Khoitul Ummaih in Baindair Laimpung during thei Covid-19 paindeimic. Thei reiseiairch meithod useid is quailitaitivei with ai caisei study aipproaich, involving in-deipth inteirvieiws with teiaicheirs, studeints, aind paireints, ais weill ais ainailysis of school prograim documeintaition. Thei reisults indicaitei thait Inteigraiteid Islaimic Eileimeintairy Schools (SDIT) Baindair Laimpung faiceid vairious chailleingeis, such ais limiteid sociail inteiraiction, difficultieis in aicceissing teichnology, aind thei disruption of sociail aind reiligious aictivitieis. Howeiveir, thei schools succeieideid in deiveiloping seiveirail innovaitions, such ais thei usei of teichnology in onlinei leiairning, projeict-baiseid leiairning, aind increiaiseid collaiboraition with paireints. Thei rolei of paireints wais ailso cruciail in supporting theiir childrein to einsurei thait chairaicteir eiducaition continueid eiffeictiveily, deispitei thei shift to onlinei leiairning. This study concludeis thait ailthough thei paindeimic poseid vairious chailleingeis, it ailso eincouraigeid thei creiaition of ai morei fleixiblei aind aidaiptivei chairaicteir eiducaition modeil thait cain bei aipplieid in thei futurei. Reicommeindaitions airei provideid to streingthein thei collaiboraition beitweiein schools aind paireints in supporting thei deiveilopmeint of studeints' chairaicteir in thei futurei.